Trend of minimally processed and ultra-processed beverages purchased in Brazilian households: Less milk and much soft drink (2002–2003 to 2017–2018) - Oliveira, Natália; Canella, Daniela Silva (Frontiers in Public Health, 2022)
The consumption of ultra-processed beverages, including sugar-sweetened and artificially sweetened ones, is associated with several health problems, which is different considering minimally processed beverages. The objective of this study was to assess the trends in the volume of minimally and ultra-processed beverages purchased for consumption in Brazilian households and their relationship with the proportion of dietary energy derived from ultra-processed foods and beverages. Drawing on data from the nationwide 2002–03, 2008–09, and 2017–18 Household Budget Surveys, the daily volume of beverages purchased per capita (milligrams) was investigated. The minimally processed beverages purchased declined over the period [2002–2003: x̄ 156.5 ml (95%CI: 148.3–164.8); 2017–2018: x̄ 101.6 ml (95%CI: 98.1–105.1)] and ultra-processed beverages were stable [2002–03: x̄ 117.9 ml (95%CI: 108.1–127.7); 2017–18: x̄ 122.8 (95%CI: 111.2–134.4)]. The most purchased beverage in 2002–2003 was milk [x̄: 154.7 ml (95%CI: 146.4–162.9)], while in 2017–2018 regular soft drinks were the most purchased [x̄: 110.7 ml (95%CI: 99.2–122.2)]. There was a decrease in the purchase of whole and skimmed milk and an increase in the purchase of other ultra-processed beverages between the periods. With the increase in the proportion of ultra-processed foods and beverages in the diet, the volume of ultra-processed beverage purchases rose and minimally processed beverages declined. The monitoring of beverage consumption and the implementation of public policies, such as taxation on ultra-processed beverages, are essential to promote improvements in health and curbing non-communicable diseases.